The Influence of Teaching Experience, Training, and Education Level on Teacher Performance through Teacher Professionalism as an Intervening Variable at SMA Negeri 1 Barabai, South Kalimantan - Kiromah, Ihda Mahya; Kadir, Abdul; Rahman, Yudi; Karsudjono, Anthonius J. (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2026)
This study aims to analyze the effect of teaching experience, educational level, and training on teacher performance. A quantitative approach with a survey method was employed in this research. Data were collected through questionnaires distributed to teachers as research respondents. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The measurement model (outer model) indicates that all research indicators meet the validity and reliability criteria, as reflected by factor loading values, composite reliability, and average variance extracted exceeding the required thresholds. Furthermore, the structural model (inner model) testing reveals that teaching experience and training have a positive and significant effect on teacher performance, while educational level shows a positive but insignificant effect. The coefficient of determination indicates that teacher performance can be moderately explained by the independent variables included in the model. These findings suggest that practical experience and competency enhancement through training play a more dominant role than formal educational background in improving teacher performance. The results are consistent with Abdul Kadir’s findings, which emphasize that professional competence development and teaching experience significantly contribute to improving teacher performance and learning quality. This study is expected to provide valuable insights for educational policymakers in designing more effective and sustainable teacher development programs.